The rise of biosimilars: Balancing innovation with affordable biologic alternatives - Alotaibi, Samar Saad; Almutairi, Nawal Hlal; Bahari, Nawal Ganai M; Almutairi, Alhanouf Zaid; Alharbi, Faisal Nasser; Almasad, Manal Nasser; Almazroa, Mashaal Nasser (International journal of health sciences, 2021)
Background: Biologics have transformed the management of immune-mediated inflammatory conditions, such as rheumatoid arthritis (RA) and inflammatory bowel disease (IBD). The introduction of biosimilars—biologic medications that are highly similar and interchangeable with approved originators—has the potential to enhance market competition and improve patient access to necessary therapies. Aim of Work: This review aims to highlight the importance of collaboration among stakeholders to optimize the benefits of biosimilars and expedite their availability to patients while ensuring safety, quality, and effectiveness. Methods: The review analyzes regulatory frameworks, market dynamics, and pharmacoeconomic assessments regarding the introduction of biosimilars. It emphasizes the role of effective communication between physicians and patients, as well as the necessity for consistent treatment recommendations and reimbursement policies. Results: The findings indicate that collaboration between regulators and developers is essential to ensure the quality and safety of biosimilars. Updating pharmacoeconomic assessments and payer policies is crucial to prevent nonmedical barriers to access. Enhanced understanding of biosimilars by patients is vital to reduce nocebo effects, while well-informed physicians can guide patients effectively through treatment transitions. Conclusion: To maintain a sustainable biosimilar market and healthcare systems, stakeholders must prioritize collaboration, operations efficiency, and information exchange.